Locoregionally Advanced, BRAF V600L–Positive, Mucosal Melanoma of the Hypopharynx Treated With a Combination of BRAF and MEK Inhibitors. (16th June 2022) - Lampasona, Giovanni; Noujaim, Jonathan; Gologan, Olga; Berdugo, Jeremie; Maniakas, Anastasios
Abstract :